Enhancing injection molding process through additive manufacturing - Ashokkumar, Ashish (My University, 2020)
Injection molding is the most common manufacturing technique used to produce polymer components in high quantities. The mold insert development is the most time-consuming phase of the injection molding process that has a high potential to be accelerated by additive manufacturing (AM). AM enables to develop mold inserts with a short lead time than the conventional manufacturing processes. Thus, design iterations in the mold insert development phase can be done more rapidly. Additive manufacturing also helps to create complex geometries that provide the opportunity to create conformal cooling channels in the mold inserts. Conformal cooling channels increases the productivity of the injection molding process by reducing the cycle time of a unit part produced. Since these channels promote uniform cooling around the part, they increase part quality and decrease scrap rate. Thus, it could be highly beneficial for a company that makes a large volume of polymer products to explore the potential of additive manufacturing. Like every other new technology, there needs to be a pre-study to understand the various implications while adapting to it. In this thesis work, the different stages of the mold insert development, which can benefit from AM, are investigated with the help of a product case study. This thesis mainly focuses on the design and prototyping of the mold inserts as well as the production of economical mold inserts. Three additive manufacturing technologies, such as poly-jetting, binder jetting, and laser powder bed fusion, are studied. The most suitable technology for each of the focused areas is selected by comparing the time to produce the mold insert, tool life of the mold inserts, and manufacturing cost. Binder jetting is selected to address the prototyping of mold insert development, and laser powder bed fusion for the economical production of the mold insert. A mold insert for the product under study is designed according to the guidelines of the respective additive manufacturing process. To address the prototyping of mold inserts, a prototype mold insert is manufactured using binder jetting. Initially, two design iterations are made to suit the prototyping of the mold insert within the budget of the thesis work. The factors that influenced the quality of the prototype were analyzed, and a third design iteration of the mold insert is proposed. To develop the production of the mold insert, injection molding simulations were done using Autodesk Moldflow advisor 2019 which follows the finite element analysis (FEA) methodology. A comparison between the conventional cooling and conformal cooling is done. The mold inserts with conformal cooling exhibited a decrease in the cycle time of the injection molding process. A solution to also manufacture the production mold insert economically with the help of additive manufacturing is proposed through the implementation of lattice structures within the mold insert. This solution is experimentally validated with the help of a prototype. A comparison of thermal behavior between a solid mold insert and a lattice filled mold insert was made. It was concluded that the lattice filled mold inserts performed better in the experiments than the solid mold inserts. Finally, the implications of additive manufacturing in its application to the injection molding industry are discussed.
Keywords: Injection molding; Additive manufacturing; mold insert development; poly-jetting; binder jetting; laser powder bed fusion; conformal cooling; Autodesk moldflow adviser 2019